A Comparative Study To Assess The Perceived Preparedness Among Male And Female Parent Regarding Adolescent Health In A Selected Urban Area. - Joshi, Anu Harshad; Kale, Kalpana (Journal of Neonatal Surgery, 2025)
BACKGROUND OF STUDY: Parenting can be the most rewarding work of adult life. Nothing brings more joy and pride than a happy, productive, and loving child. Each age and stage of a child's development has specific goals and tasks. For infants, it is to eat, sleep, and explore their world. For adolescents, it is to become their own person with their own group of friends. Adolescents need many skills in order to successfully achieve their goal of increased independence. Some adolescents do not make this transition smoothly. Their movement toward independence can cause stress and grief for parents and families. Some aspects of this rough transition are normal and, while stressful, should not alarm parents. Advances in neuroscience tell us that the plasticity of the adolescent brain presents “a second opportunity” to positively influence long-term outcomes and even reverse some of the effects of adverse childhood experiences (ACEs) Supported and challenged by parents and caregivers who love them unconditionally, adolescents have the relational connection required to build on their strengths to develop competencies that enhance their resilience and give them the confidence, character, knowledge and skills they need to cope with adversity, realise their full developmental potential, and contribute to family and society.AIM; To compare the perceived preparedness of male and female parents regarding adolescent health. MATERIALS AND METHODS: In this study, Quantitative approach and comparative design is adopted to compare the perceived preparedness of male and female parents regarding adolescent health. The study is conducted in households located in urban areas of Maharashtra state. A total of 100 samples (50 male and 50 female parents) who satisfied the inclusion criteria were recruited using non-probability convenient sampling technique from study population. A validated 5- point Likert scale was used to assess the perceived preparedness of the male and female parents. Data were analysed using descriptive statistics and inferential statistics. RESULT: Among the 100 parents, 50 (50%) were males and 50 (50%) were females. An independent samples t-test was used to compare preparedness scores between male and female parents. Female parents demonstrated significantly higher preparedness scores (84.70 ± 8.11) than male parents (72.52 ± 7.84). The obtained t-value was -6.79 with a p-value less than 0.001, indicating a statistically significant difference between the two groups. Thus female parents showed higher preparedness levels compared to male parents.